2015
DOI: 10.12659/msm.895346
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Patients with Gastroesophageal Reflux Disease Refractory to Proton Pump Inhibitors and the Effects of Switching to 20 mg Esomeprazole on Reflux Symptoms and Quality of Life

Abstract: BackgroundRefractory gastroesophageal reflux disease (GERD) may deteriorate patient quality of life (QOL) despite proton pump inhibitor (PPI) therapy.Material/MethodsNineteen Japanese institutions were surveyed to determine the clinical characteristics and QOL of patients with refractory GERD. Those patients treated with a conventional PPI were switched to 20 mg esomeprazole for 4 weeks. Symptoms and QOL were assessed using Global Overall Symptom and Gastrointestinal Symptom Rating Scale (GSRS) questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…42,43 The increased prevalence of functional and psychosomatic disorders among women may account in part for their increased odds of persistent GERD symptoms while on PPIs, as seen in our study. 43 With regard to age, a Japanese study found that older age was more associated with PPI-resistance, 44 which is contrary to our findings. The higher prevalence of PPIrefractory GERD symptoms among younger individuals in our population may again be explained by the higher prevalence of somatization and functional disorders among this group, 43 where PPIs are unlikely to improve esophageal symptoms.…”
Section: Discussioncontrasting
confidence: 99%
“…42,43 The increased prevalence of functional and psychosomatic disorders among women may account in part for their increased odds of persistent GERD symptoms while on PPIs, as seen in our study. 43 With regard to age, a Japanese study found that older age was more associated with PPI-resistance, 44 which is contrary to our findings. The higher prevalence of PPIrefractory GERD symptoms among younger individuals in our population may again be explained by the higher prevalence of somatization and functional disorders among this group, 43 where PPIs are unlikely to improve esophageal symptoms.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies had revealed that RGERD was more strongly related with weakly acid reflux and alkaline reflux than acid reflux. 6,24,38,39 Furthermore, long term usage of PPI might reduce the detective acid reflux episodes difference between the 2 groups. In addition, only 48 patients were enrolled in our study, and the small sample size might be related with the results.…”
Section: Discussionmentioning
confidence: 99%
“…Another clustered randomization trial conducted in Canada indicated that switching the PPI to esomeprazole would result in a mean 0.071 (95% CI 0.091–0.051, P < 0.0001) gain in quality‐adjusted life months compared with continuing with another PPI (other than esomeprazole and lansoprazole) or H2RA therapy 72 . Another small uncontrolled study from Japan also suggested that switching PPI would improve reflux symptom 73 …”
Section: Methodsmentioning
confidence: 99%